2016
DOI: 10.1124/jpet.116.232553
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Anandamide by Human Cytochrome P450 2J2 in the Reconstituted System and Human Intestinal Microsomes

Abstract: According to the Centers for Disease Control and Prevention, the incidence of inflammatory bowel diseases (IBD) is about 1 in 250 people in the United States. The disease is characterized by chronic or recurring inflammation of the gut. Because of the localization of the endocannabinoid system in the gastrointestinal tract, it may be a potential pharmacologic target for the treatment of IBD and other diseases. Fatty acid amide hydrolase (FAAH) is a potential candidate because it is upregulated in IBD. FAAH hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…3D). The total turnover rates of AEA, EPEA, and DHEA are significantly greater than those of AA, EPA, and DHA (28,32,56). Specifically, maximal CYP2J2 conversion of DHA to 19,20-EDP was calculated at 22.5 pmol·min −1 ·pmol −1 protein (57), whereas the CYP2J2 conversion of DHEA to 19,20-EDP-EA was 542.3 ± 44.6 5 pmol·min −1 ·pmol −1 protein, thus demonstrating that the preference for the DHEA substrate is an order of magnitude greater than the preference for DHA.…”
Section: Discussionmentioning
confidence: 99%
“…3D). The total turnover rates of AEA, EPEA, and DHEA are significantly greater than those of AA, EPA, and DHA (28,32,56). Specifically, maximal CYP2J2 conversion of DHA to 19,20-EDP was calculated at 22.5 pmol·min −1 ·pmol −1 protein (57), whereas the CYP2J2 conversion of DHEA to 19,20-EDP-EA was 542.3 ± 44.6 5 pmol·min −1 ·pmol −1 protein, thus demonstrating that the preference for the DHEA substrate is an order of magnitude greater than the preference for DHA.…”
Section: Discussionmentioning
confidence: 99%
“…[31]. It was also shown that AA was a moderate inhibitor of CYP2J2-mediated metabolism of AEA [31]. The authors found that 5,6-EET-EA is a potent cannabinoid receptor-2 agonist.…”
Section: Endogenous Substrates Of Cyp2j2mentioning
confidence: 99%
“…CYP2J2 is an epoxygenase enzyme metabolizing a number of polyunsaturated omega-6 (ω-6) fatty acids such AA and LA and omega-3 (ω-3) fatty acids such as eicosapentaenoic acid (EPA) [20] and docosahexaenoic acid (DHA) [21]. [31]. It was also shown that AA was a moderate inhibitor of CYP2J2-mediated metabolism of AEA [31].…”
Section: Endogenous Substrates Of Cyp2j2mentioning
confidence: 99%
“…9,17,20 Specifically, AEA and 2-AG interact with CYPs and undergo epoxidation to their more bioactive products, EET-EA and EET-G with varied biological activities. 16,20,2426 These metabolites are targets of both FAAH and soluble epoxide hydrolase (sEH) which degrades CYP epoxygenase-derived eCB metabolites to yield the corresponding diol product, which is a current target for the development of anti-inflammatory drugs. 5,14,27,28 …”
Section: Introductionmentioning
confidence: 99%